Pheochromocytoma presenting as fulminant myocarditis mimicking COVID‐19 pneumonia - Imen Rojbi (Wiley, 2021)
Abstract Adrenergic cardiomyopathy is uncommon but can be fulminant and life‐threatening. Nowadays, the need to exclude the possibility of COVID‐19 pneumonia in patients with acute dyspnea in a previously healthy adult may cause a delay in the diagnosis.